2016
DOI: 10.1021/acs.energyfuels.6b00061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Ores on the Pyrolysis Characteristics of a Low-Rank Bituminous Coal

Abstract: This work investigates the effects of two kinds of iron ore on the pyrolysis characteristics of a low-rank bituminous coal from Hami, China. The pyrolysis and its product distribution were studied using a thermogravimetric analyzer and a fixed bed reactor. A gas chromatograph and a gas chromatograph–mass spectrometer were employed to test the properties and composition of the pyrolytic products. Results showed that the pyrolysis temperature of the raw coal ranged mainly from 350 to 650 °C. The weight-loss rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It is reported that the pyrolysis characteristics of coal could be clearly reflected by the kinetic parameters based on temperature region among the maximum reaction rate in the second stage of pyrolysis reaction. Therefore, the pyrolysis temperature range of 370°C to 470°C was used to study the kinetic parameters in this work.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the pyrolysis characteristics of coal could be clearly reflected by the kinetic parameters based on temperature region among the maximum reaction rate in the second stage of pyrolysis reaction. Therefore, the pyrolysis temperature range of 370°C to 470°C was used to study the kinetic parameters in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, the catalytic influence of Fe-based catalyst lead to the rise of EX conversion and reduction of the final temperature. Multiple studies [25][26][27] showed that Fe-based catalysts have the capability of cracking the long-chain aliphatic hydrocarbons and lowering the bond energy, thereby making the pyrolysis reaction occur at lower temperature.…”
Section: Thermal Behaviors Of Extract With/without Catalystmentioning
confidence: 99%
“…The light tar yield could be improved by coupling of in-situ catalytic cracking and the process of ethane steam reforming on the carbon-based catalyst (Zhao, Li et al 2016). Meanwhile, the methods for increasing tar yield and its quality were supposed such as strengthen the structure of volatiles and the control of composition, design a novel pyrolysis reactor to regulate the pyrolysis of coal particles and the secondary reaction process of volatiles, coordinately control pyrolysis conditions, control the dust content in oil and gas, etc (Yang, Fu et al 2015).…”
Section: Introductionmentioning
confidence: 99%